2004
DOI: 10.1021/bc034189q
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Trajectories of Peptide-Modified Gold Particle Complexes:  Comparison of Nuclear Localization Signals and Peptide Transduction Domains

Abstract: Gold nanoparticles modified with nuclear localization peptides were synthesized and evaluated for their subcellular distribution in HeLa human cervical epithelium cells, 3T3/NIH murine fibroblastoma cells, and HepG2 human hepatocarcinoma cells. Video-enhanced color differential interference contrast microscopy and transmission electron microscopy indicated that transport of nanoparticles into the cytoplasm and nucleus depends on peptide sequence and cell line. Recently, the ability of certain peptides, called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
386
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(399 citation statements)
references
References 22 publications
9
386
2
2
Order By: Relevance
“…[6,7] AuN were used as markers for tracking signal transduction in cells, which also suggests their non-toxic nature. [8,9] The AuN of diameter of 13 nm, covered by oligonucleotides were used for gene regulation. [10] Bulk gold is widely regarded as 'safe' and chemically inert, and, produced as drugs, have been used, inter alia, in the treatment of rheumatic diseases already in the seventies of the twentieth century.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] AuN were used as markers for tracking signal transduction in cells, which also suggests their non-toxic nature. [8,9] The AuN of diameter of 13 nm, covered by oligonucleotides were used for gene regulation. [10] Bulk gold is widely regarded as 'safe' and chemically inert, and, produced as drugs, have been used, inter alia, in the treatment of rheumatic diseases already in the seventies of the twentieth century.…”
Section: Introductionmentioning
confidence: 99%
“…A severe increase in cell death has only been observed in particles of a diameter of 1.4 and 1.2 nm, which can be regarded as gold atom clusters rather then nanoparticles (15). However, a low-level toxicity was reported in several cell lines after using nanoparticles of various sizes and in different concentrations (9,10,16). Most toxicity studies as yet have used chemically generated GNPs, which need a surface coating to avoid aggregation or are conjugated to ligands like residual reduction agents and additives.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles' exposure at 150 pm for 3 h on HeLa and 3T3/NIH cells resulted in cell viability reduction by 20 and 5%, respectively [153]. In another study, gold nanoparticles were exposed to macrophage cells with particle size range 10-100 µm for 24-72 h. The study demonstrated that the 100 µm nanoparticles decreased the cell viability to 85% in 72 h [154].…”
mentioning
confidence: 96%